2008
DOI: 10.1002/chem.200801429
|View full text |Cite
|
Sign up to set email alerts
|

β‐Cyclodextrin‐Appended Giant Amphiphile: Aggregation to Vesicle Polymersomes and Immobilisation of Enzymes

Abstract: A giant amphiphile consisting of polystyrene end-capped with permethylated beta-cyclodextrin was synthesised and found to form vesicular structures when injected as a solution in THF into water. The ability of the cyclodextrins on the surface of the polymersomes to form inclusion complexes with hydrophobic compounds was tested by carrying out a competition experiment with a fluorescent probe sensitive to the polarity of the surrounding medium. It was found that 1-adamantol can displace the fluorescent probe fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 25 publications
0
56
0
Order By: Relevance
“…Polymer/enzyme conjugates based on b-CD were presented by Feiters and co-workers [130] as well as Chen and coworkers. [131] Thel atter group showed the supramolecular attachment of adamantyl-functionalized PNIPAM or POEGMA to pyrophosphatase with preserved enzyme activity.A deli and co-workers utilized b-CD/polyglycerol conjugates to form supramolecular complexes with human serum albumin.…”
Section: Nanoparticles and Hybrid Materialsmentioning
confidence: 99%
“…Polymer/enzyme conjugates based on b-CD were presented by Feiters and co-workers [130] as well as Chen and coworkers. [131] Thel atter group showed the supramolecular attachment of adamantyl-functionalized PNIPAM or POEGMA to pyrophosphatase with preserved enzyme activity.A deli and co-workers utilized b-CD/polyglycerol conjugates to form supramolecular complexes with human serum albumin.…”
Section: Nanoparticles and Hybrid Materialsmentioning
confidence: 99%
“…Oligohistidine sequence Complexation PDB-b-PEG [37,38] Fluorescein labeled maltose binding protein [37], eGFP [37,38], RFP [38] Cyclodextrin (CD) Adamantane Hydrophobic interactions PS-CD [39], CD-PEI-CD [40] HRP [39], PEG [40] N-hydroxysuccinimidyl ester Thiol C-S bond PCL-b-PEG [41] Antibody OX26 [41] Vinyl sulfone Thiol C-S bond PEG-b-PMCL [42] Cysteine-RGD peptide [42] …”
Section: Conjugation To Preformed Polymersomesmentioning
confidence: 99%
“…PS homopolymer terminated with a permethylated β-cyclodextrin (β-CD) group [39], as well as polyether imide (PEI) terminated at both chain ends with β-CDs [40] self-assembled into polymersomes, due to the hydrophilicity of the carbohydrate headgroups and the hydrophobicity of the polymer. The surface of these vesicles is a corona of β-CDs, which allowed the conjugation of adamantane-tagged horse radish peroxidase [39] and adamantane-terminated PEG [40]. Isothermal titration calorimetry (ITC) and static light scattering (SLS) revealed that both the inner and the outer polymersome surfaces were modified with the PEG.…”
Section: Aminementioning
confidence: 99%
See 1 more Smart Citation
“…By incorporation of theses ynthetic receptors on as olids upport, proteins containing the correspondingl igand can be immobilized. [20,26,[31][32][33][34][35][36][37][38][39] There are, however, only very limited examples of the use of supramolecular chemistry fort he immobilization of proteins on lipid bilayers. The potentialo f as upramolecular approach forp rotein immobilization on lipid membranes is most impressively illustrated by the membrane incorporation of nitrilotriacetic acids that recruit His 6 -tagged proteins upon addition of nickel.…”
Section: Introductionmentioning
confidence: 99%